ETHNOCULTURAL FEATURES IN THE CREATION OF FEMALE CHARACTERS - Umida Abdullayeva Abdumutal qizi (Web of Journals Publishing, 2025)
This article explores the ethnocultural characteristics in the portrayal of female characters in Eastern historical-biographical literature, focusing specifically on the novel Yulduzli Tunlar by Pirimqul Qodirov and its English translation by Carol Ermakova. It examines how female figures such as Khanzoda Begim, Gulbadan Begim, and Qutlug’ Nigorxonim are depicted not only as historical personalities but also as cultural archetypes, political intermediaries, and bearers of ethnic and religious identity within the Timurid and Babur dynasties. The study highlights the translator’s strategies in preserving cultural specificity through transliteration of names and titles, and in maintaining somatic and emotional metaphors essential to the original text’s meaning. By employing a feminist and postcolonial translation framework, the article argues that Ermakova’s translation acts as a cultural bridge that resists orientalist stereotypes and restores the voices of historically marginalized women. The translation is presented as a form of cultural rehabilitation and feminist historiography that fosters intercultural dialogue between Eastern and Western readers, emphasizing the importance of cultural context and ideological sensitivity in literary translation.
Keywords: Ethnocultural identity, female characters, Eastern literature, historical-biographical novel, Yulduzli Tunlar, Carol Ermakova, translation strategies, feminist translation, postcolonial theory, cultural rehabilitation, somatic metaphors, cultural specificity, transliteration, political intermediaries, Timurid and Babur dynasties, intercultural dialogue, orientalist stereotypes, feminist historiography.